War room : prayer is a powerful weapon - Kendrick, Alex, 1970-; Kendrick, Stephen, 1973-; Shirer, Priscilla, 1974-; Stallings, T. C., 1977-; Abercrombie, Karen, 1956-; Michael Jr., 1986-; Harris, Jadin; Downing, Tenae, 1981-; Pitts, Alena, 2004-; Blamy, Dave; Ricks, Lee, 1921-1998; Kendrick, Alex; et al. ([Culver City, CA] : Sony Pictures Home Entertainment, 2016)
Tony and Elizabeth Jordan have it all; great jobs, a beautiful daughter, and their dream house. But appearances can be deceiving. Their world is actually crumbling under the strain of a failing marriage. While Tony basks in his professional success and flirts with temptation, Elizabeth resigns herself to increasing bitterness. But when Elizabeth meets her newest client, Miss Clara, she is challenged to establish a "war room" and a battle plan of prayer for her family. As Elizabeth tries to fight for her family, Tony's hidden struggles come to light. Tony must decide if he will make amends with his family and prove Miss Clara's wisdom that victories don't come by accident.
In English, Portuguese, Spanish, Thai with optional Chinese simplified, Chinese traditional, English, Korean, Portuguese; English SDH.
Priscilla Shirer, T.C. Stallings, Karen Abercrombie, Michael Jr., Jadin Harris, Tenae Downing, Alena Pitts, Alex Kendrick, Dave Blamy.
Music, Paul Mills ; edited by Alex Kendrick, Stephen Hullfish ; director of photography, Bob M. Scott.
Title from container.
DVD release of the 2015 motion picture.
Anamorphic widescreen (2.40:1) presentation.
Keywords: Religious films; Feature films; Christian films; Christianity -- Drama; Prayer -- Drama; Married people -- Drama; Fiction films; Video recordings for the hearing impaired